Mechanical behavior of spiral reinforcement recycled aggregate concrete round columns under axial compression after spraying water at high temperatures - Wang, Xin; Li, Junya; Huang, Leiqun; Xie, Wangjun; Chen, Zongping (Frontiers in Materials, 2022)
The mechanical behavior of spiral reinforcement recycled aggregate concrete round columns under axial compression after spraying water at high temperatures cooling was investigated. Three parameters including recycled coarse aggregate replacement ratio, temperature, and pitch of screw stirrups were taken into consideration. 26 specimens (18 specimens cooled by water spray after high temperature, 6 specimens cooled naturally after high temperature, and 2 specimens compared at room temperature) were designed for static loading test. The failure modes of regenerated concrete columns with spiral reinforcement were observed after cooling by high-temperature water spraying. The mechanical properties such as peak load, peak displacement, initial stiffness and displacement ductility coefficient under different cooling modes at high temperatures were obtained. The mechanical properties of the specimens with different parameters were analyzed. The calculation method of bearing capacity of regenerated spiral reinforced concrete columns cooled by high-temperature water spraying is discussed. The results indicate that after cooling by water spraying, a large number of irregular cracks and white smoke appear in the regenerated concrete columns with the spiral reinforcement. It is shown that although the replacement rate of recycled coarse aggregate has little effect on the peak load of the recycled concrete cylinders with spiral reinforcement after cooling by water spraying at high temperatures, it greatly influences the peak displacement. It also indicates that with the increase in temperature, the initial stiffness of the regenerated concrete cylinder with spiral reinforcement decreases continuously. Furthermore, The higher the pitch of the helical stirrup, the lower the peak load and ductility coefficient of the regenerated concrete cylinder, and the peak displacement of natural cooling is always larger than that of spray cooling under the same conditions.